A number theory problem by Bryan Lee Shi Yang

Find (y^x)(y^-x). The answer will always be......


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Aryan Gaikwad
Feb 20, 2015

= x y × x y = x y y = x 0 = 1 =\quad { x }^{ y }\times { x }^{ -y }\\ =\quad x^{ y-y }\\ ={ \quad x }^{ 0 }\quad =\quad 1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...